Peran Komunikasi Interpersonal Pelatih terhadap Proses Adaptasi Member Pemula DX Boxing Jakarta - Romario Gominta Manurung; Sari Ekowati (Indo Green Journal, 2026)
Interpersonal communication plays a vital role in building effective relationships between coaches and beginner members during the training process. This study aims to analyze the role of coaches’ interpersonal communication in supporting beginners’ adaptation at DX Boxing Jakarta, identify the forms of adaptation experienced by new members, and examine the obstacles encountered by coaches throughout the process. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving coaches, beginner members, and individuals familiar with the training process. The analysis was based on Joseph A. DeVito’s Interpersonal Communication Theory, emphasizing openness, empathy, supportiveness, positiveness, and equality, as well as Judee K. Burgoon’s Interaction Adaptation Theory using the Requirements, Expectations, and Desires (RED) framework. The findings reveal that coaches’ interpersonal communication significantly supports beginners’ adaptation. Openness, empathy, encouragement, positive motivation, and equal treatment foster members’ confidence, comfort, and engagement during training. The adaptation process is also influenced by each member’s individual requirements, expectations, and personal goals. Key challenges include differences in personality, self-confidence, physical ability, and anxiety during initial training sessions. These obstacles are addressed through persuasive communication, individualized guidance, and continuous motivation, enabling beginner members to adapt more effectively and participate confidently in the training program.